Functional and Antimicrobial Properties of Propolis from Different Areas of Romania - Gianluca Albanese; Alexandru Ioan Giurgiu; Otilia Bobiș; Adriana Cristina Urcan; Sara Botezan; Victorița Bonta; Tudor Nicolas Ternar; Claudia Pașca; Massimo Iorizzo; Antonio De Cristofaro; Emilio Caprio; Daniel Severus Dezmirean (Applied Sciences)
Propolis is a complex resinous substance produced by Apis mellifera L. through a process of mixing tree resins with saliva and beeswax. This substance plays a crucial role in the hive’s defence against a range of pathogenic agents, maintaining a consistent internal temperature and aseptic environment for the bee colony. The objective of the present study was to assess the chemical composition and antibacterial characteristics of five hydroalcoholic propolis extracts sourced from diverse geographic regions within Romania. This study shows that the biological and functional properties of propolis extracts are related to the plant resources in the vicinity of the hives, and this relates to greater or lesser bioactivity of the extracts; therefore, to standardise the extracts, it is essential to catalogue the plant essences in the proximity of the hives. The antimicrobial activity of propolis extract from each apiary was evaluated against five Gram-positive, five Gram-negative bacteria, and one fungal strain, using the difuzimetric method and minimum inhibitory concentration (MIC). The results showed some variability, supporting the hypothesis that not only may the botanical origin influence the properties of propolis but also that a higher number of flavonoids influences the higher antimicrobial activity in the extracts.